UNIVERSITY TEACHER'S READINESS FOR DIGITAL TRANSFORMATION OF THE EDUCATIONAL PROCESS - Tatiana V. Gromova (Russian Journal of Education and Psychology)
Background. Successful professional activity of a university teacher is impossible without productive and innovative use of information and communication technologies (ICT). This process involves not only the constant widespread dissemination of knowledge and information, their transformation into digital educational products, but also the teacher's ability and readiness to effectively organize the educational process in new conditions. We suppose the digital readiness of the university teacher should be the subject of systematic scientific analysis.